Contribution of Adipose Tissue to the Chronic Immune Activation and Inflammation Associated With HIV Infection and Its Treatment - Bourgeois, Christine; Gorwood, Jennifer; Olivo, Anaelle; Le Pelletier, Laura; Capeau, Jacqueline; Lambotte, Olivier; Béréziat, Véronique; Lagathu, Claire (Frontiers in Immunology, 2021)
White adipose tissue (AT) contributes significantly to inflammation – especially in the context of obesity. Several of AT’s intrinsic features favor its key role in local and systemic inflammation: (i) large distribution throughout the body, (ii) major endocrine activity, and (iii) presence of metabolic and immune cells in close proximity. In obesity, the concomitant pro-inflammatory signals produced by immune cells, adipocytes and adipose stem cells help to drive local inflammation in a vicious circle. Although the secretion of adipokines by AT is a prime contributor to systemic inflammation, the lipotoxicity associated with AT dysfunction might also be involved and could affect distant organs. In HIV-infected patients, the AT is targeted by both HIV infection and antiretroviral therapy (ART). During the primary phase of infection, the virus targets AT directly (by infecting AT CD4 T cells) and indirectly (via viral protein release, inflammatory signals, and gut disruption). The initiation of ART drastically changes the picture: ART reduces viral load, restores (at least partially) the CD4 T cell count, and dampens inflammatory processes on the whole-body level but also within the AT. However, ART induces AT dysfunction and metabolic side effects, which are highly dependent on the individual molecules and the combination used. First generation thymidine reverse transcriptase inhibitors predominantly target mitochondrial DNA and induce oxidative stress and adipocyte death. Protease inhibitors predominantly affect metabolic pathways (affecting adipogenesis and adipocyte homeostasis) resulting in insulin resistance. Recently marketed integrase strand transfer inhibitors induce both adipocyte adipogenesis, hypertrophy and fibrosis. It is challenging to distinguish between the respective effects of viral persistence, persistent immune defects and ART toxicity on the inflammatory profile present in ART-controlled HIV-infected patients. The host metabolic status, the size of the pre-established viral reservoir, the quality of the immune restoration, and the natural ageing with associated comorbidities may mitigate and/or reinforce the contribution of antiretrovirals (ARVs) toxicity to the development of low-grade inflammation in HIV-infected patients. Protecting AT functions appears highly relevant in ART-controlled HIV-infected patients. It requires lifestyle habits improvement in the absence of effective anti-inflammatory treatment. Besides, reducing ART toxicities remains a crucial therapeutic goal.